The transfer mechanism of land and buildings tax management from the central to the local administration: A case study at the city of Yogyakarta. - Oby Dinata (FH 14 UMY 018, 2014)
*18 To support the local autonomy policy, then the Central Government transferred the management of Land and Buildings Tax as the Local Tax. In Indonesia, there are several City/Region that have been managed the Land and Buildings Tax independently. One of those cities is Yogyakarta City. In 2012 Yogyakarta City is one of 17 cities in Indonesia which was appointed as a pilot project in managing Land and Buildings Tax as the Local Tax. The purposes of this research are to understand deeply on the process of management transfer of Land and Buildings Tax management from the Central Government to the Local Government at the City of Yogyakarta, and tounderstand about the management and collection system of land and buildings tax post of transfer management from the Central Government to the Local Government at the City of Yogyakarta. The methods of this research are normative and emprical legal research. The result of this research shows that there were several preparations that had done by the City of Yogyakarta as the receiver of authority to managing and collecting the Land and Buildings Tax. Furthermore, post of transfer management, the Management and Collection System of Land and Buildings Tax still adopted the previous system as managed by the Central Government. Key Words: Land and Buildings Tax, Process of Management Transfer, Management and Collection System, Yogyakarta City.